Real‐world outcomes of rapid regional hepatitis C virus treatment scale‐up among people who inject drugs in Tayside, Scotland. Issue 5 (8th December 2021) - Byrne, Christopher J.; Beer, Lewis; Inglis, Sarah K.; Robinson, Emma; Radley, Andrew; Goldberg, David J.; Hickman, Matthew; Hutchinson, Sharon; Dillon, John F.
Summary: Background: In 2017, Tayside, a region in the East of Scotland, rapidly scaled‐up Hepatitis C Virus (HCV) outreach and treatment among People Who Inject Drugs (PWID) using novel community care pathways. Aims: We aimed to determine treatment outcomes for PWID during the scale‐up against pre‐determined targets; and assess re‐infection, mortality, and post‐treatment follow up. Methods: HCV treatment was delivered in community pharmacies, drug treatment centres, nurse‐led outreach clinics, prisons, and needle exchanges, alongside conventional hospital care. We retrospectively analysed clinical outcomes and compared pathways using logistic regression models. Results: Of 800 estimated HCV‐infected PWID, 718 (90%) were diagnosed. 713 treatments commenced among 662 (92%) PWID, delivering 577 (81%) Sustained Virologic Responses (SVR). SVR was 91% among those who attended for testing. Forty‐six individuals were treated more than once. Needle exchanges and community pharmacies initiated 49% of all treatments. Regression analyses implied pharmacies had superior follow‐up, but there was no difference in likelihood of achieving SVR in community pathways relative to hospital care. Re‐infection occurred 39 times over 256.57 person years (PY), yielding a rate of 15.20 per 100 PY (95% CI 10.81‐20.78). 54 deaths occurred (29 drug related) over 1, 553.04 PY, yielding a mortality rate of 3.48 per 100 PY (95% CI 2.61‐4.54). Drug‐related mortality was 1.87 per 100 PY (95% CI 1.25‐2.68). Conclusions: Rapid HCV treatment scale‐up to PWID in community settings, whilst maintaining high SVR, is achievable. However, other interventions are required to minimise re‐infection; reduce drug‐related deaths; and improve post‐SVR follow‐up testing regionally. Abstract : Rapid regional HCV treatment scale‐up was achieved in Tayside. There were over 700 treatments across six pathways in three years, a close to two‐fold increase on previously high levels of HCV treatment among PWID. The estimated care cascade shows that 90% of the estimated HCV‐infected PWID population were diagnosed and 92% of those initiated treatment. SVR in the ITT group was over 80% and exceeded 90% in those with a documented test.